1991
DOI: 10.1161/01.cir.84.6.2294
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of normal coronary artery dimensions in humans.

Abstract: Linear regression analysis showed that coronary vessel cross-sectional area and total coronary cross-sectional area increase with regional myocardial mass and decrease linearly with age. Multivariate regression analysis revealed that regional myocardial mass and age were independent predictors of cross-sectional area for each vessel and for the total coronary cross-sectional area. We speculate that age-related decline in physical activity, in part, may be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 38 publications
4
57
1
Order By: Relevance
“…[4] Lumen diameter of normal human coronary arteries and several factors affecting their lumen diameters have previously been studied in different countries on different populations. [5][6][7][8][9][10] To the best of our knowledge, there is no study with international recognition regarding normal …”
mentioning
confidence: 99%
“…[4] Lumen diameter of normal human coronary arteries and several factors affecting their lumen diameters have previously been studied in different countries on different populations. [5][6][7][8][9][10] To the best of our knowledge, there is no study with international recognition regarding normal …”
mentioning
confidence: 99%
“…The mean sectional areas of LMCA, LAD, and CX were found as 17 2 in men, respectively. We compared cross-sectional areas of arteries among both genders and found no statistical difference for CX (P = 0.094), while LMCA and LAD cross sectional areas were larger in men (P < 0.001, for both).…”
Section: Resultsmentioning
confidence: 90%
“…Leung et al (17) reported no significant correlation between coronary artery dimensions and weight, height, or body surface area, while Zeina et al (10) reported significant correlation between LMCA cross-sectional area and height, weight, and body surface area in males only.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study showed that whilst conventional TTE failed to adequately assessed the coronary ostia of these patients, an alternative novel TTE acoustic window was able to visualize most of the coronary ostia, thus providing a potentially suitable alternative noninvasive imaging tool to monitor the coronary ostial dilation long-term. The normal diameter of native coronary vessels can be underestimated in post-mortem and conventional invasive angiographic studies [11][12][13][14]. These studies usually assess only the mid-portion of the proximal segment of the coronary vessels rather than the ostium (the aortocoronary junction), and report diameters of 2-5 mm for the RCA and 4-7 mm for the LMA.…”
Section: Discussionmentioning
confidence: 99%